Representation of agricultural density maps of grain crops in Nineveh governorate using Geographic information systems - Bilal Jalal Basher (Genius Journals, 2024)
The study attempts to demonstrate the importance of the map in representing the agricultural density of the study area (Nineveh), because the map, with its two parts, is considered one of the effective means adopted by the researcher or geographer in representing geographical phenomena, both natural and human, and the use of geographic information systems(Gls) in cartographic representation and creating a database for grain crops, in Nineveh Governorate, and showing the areas with the most agricultural density, as well as clarifying that the workforce has an important role in the development and production of agricultural crops, starting from the plowing and sowing stage all the way to the harvesting and marketing stage, and thus the population has a major impact on the agricultural production process, as they are considered the producers of these crops, agricultural crops and their consumers at the same time, which is reflected in the volume of agricultural production of these agricultural crops and consumers of them at the same time, which is reflected in the volume of agricultural production of these agricultural crops in terms of quantity and quality
Keywords: agricultural; attempts; demonstrate; importance